Molar-root incisor malformation - a systematic review of case reports and case series - Emilija D. Jensen; Gabrielle Smart; Brianna F. Poirier; Sneha Sethi (BMC, 2023)
Abstract Objectives Molar-root incisor malformation (MRIM) is a seldom reported condition characterised by disturbances in root development of first permanent molars. This systematic review aimed to collate the clinical characteristics of individuals diagnosed with MRIM. Materials and methods A systematic search strategy using PubMed, Embase, Web of Science, and SCOPUS databases was performed through to March 2023. Inclusion criteria were case reports or case series including a diagnosis consistent with MRIM. Critical appraisal for all included studies utilised the Joanna Briggs Institute (JBI) critical appraisal checklist for case reports and case series and collation of clinical characteristics was performed in JBI System for the Unified Management, Assessment and Review of Information program. Results The search identified 157 studies from which 35 satisfied the inclusion criteria. After full-text review, a total of 23 papers described the MRIM dental anomaly and were included in this paper. A total of 130 reported cases were retrieved, with age ranging 3-32 years, and males affected 1.16:1 females. Presence of neurological conditions, premature birth history, medication, and surgery within first years of life were synthesised and described. Conclusions The aetiology of MRIM is yet to be determined but epigenetic changes from significant medical history in the first years of life are likely to influence the development of this root malformation. First permanent molars were most commonly affected, but clinicians should be aware that permanent central incisors, primary teeth and other permanent teeth may also be affected.